Bufotoxin poisoning that showed the sign of acute digitalis overdose in the patient of Kyushin® intoxication. Issue 3 (May 2020) - Cha, Kyungman; So, Byung Hak; Jeong, Won Jung
Introduction: Kyushin ® is a widely used herbal medicine in East Asia for heart failure. Toad venom in present in Kyushin ®, which has positive inotropic effect as digitoxin. Case presentation: An 81-year-old, female patient presented with decreased mental status after overdose of Kyushin ® . The first electrocardiogram showed junctional tachycardia with 142/min, suddenly dropped to 27/min and followed by ventricular fibrillation. After one cycle of CPR, spontaneous circulation returned but junctional bradycardia, tachycardia, and ventricular fibrillation appeared. After six times of defibrillation, spontaneous circulation returned, and mechanical ventilator and transcutaneous pacing were applied. Plasma toxicology test revealed digitoxin 66.90 ng/mL by cloned enzyme donor immunoassay and digoxin 0.76 ng/mL by kinetic interaction of microparticles in solution immunoassay. After 8 h from presentation, the patient's mental status came to be alert, and then transcutaneous pacing was removed. Discussion: Cloned enzyme donor immunoassay has been reported to be highly cross-reactive with digoxin-like substances, which strongly supports bufotoxin to be responsible for arrhythmia of the patient. Conclusion: Poisoning of bufotoxin in Kyushin ® can cause cardiac arrhythmia, even arrest, but without digoxin-specific Fab, conventional therapy could be successful.